Multistate unfolding of alpha-mannosidase from Canavalia ensiformis (Jack Bean): evidence for the thermostable molten globule - Kumar, Avinash; Gaikwad, Sushama M. (Biochemical and Biophysical Research Communications, 2010)
The relevance of partially ordered states of proteins (such as the molten-globule state) in cellular processes is beginning to be understood. We examined the conformational transitions in a multimeric and high molecular weight class II alpha-mannosidase from Canavalia ensiformis (Jack Bean) (Jb alpha-man) utilizing intrinsic fluorescence, solute quenching, hydrophobic dye binding, size exclusion chromatography and circular dichroism (CD) spectroscopy for the protein in presence of Guanidine hydrochloride (GdnHCl). The decomposition analysis of the protein spectra obtained during unfolding showed progressive appearance of class S, I, II and III trp. The parameter A and spectral center of mass showed multi state unfolding of the protein and phase diagram analysis revealed formation of an intermediate of Jb alpha-man in the vicinity of 1 M GdnHCl. The intermediate exhibited compact secondary and distorted tertiary structure with exposed hydrophobic amino acids on the surface, indicating the molten-globule nature. The dissociation, partial unfolding and aggregation of Jb alpha-man occurred simultaneously during chemical denaturation. The molten-globule possessed slightly higher hydrodynamic radius, perturbance in the structure up to 60 degrees C and stability of the structure up to 80 degrees C unlike the native Jack Bean alpha-mannosidase. The modes of chemical and thermal denaturation of the native protein were different. The solute quenching parameters confirmed the altered confirmation of the intermediate. Taken together, our results constitute one of the early reports of formation of GdnHCl induced molten globule in a class II alpha-mannosidase. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: alpha-Mannosidase; Circular dichroism; fluorescence; Guanidine hydrochloride; Molten globule; Thermostability; Unfolding

Molecular cloning and in silico studies of physiologically significant trehalase from drosophila melanogaster - Shukla, Ekta; Thorat, Leena; Bhavnani, Varsha; Bendre, Ameya D.; Pal, J. K.; Nath, B. B.; Gaikwad, Sushama M. (International Journal of Biological Macromolecules, 2016)
Trehalase, a physiologically important glycosidase is known for its crucial role in insect glycometabolism and stress recovery. The present study describes the molecular cloning of a gene fragment, encoding the catalytically active trehalase from Drosophila melanogaster (DmTre) and its heterologous expression in Escherichia coli. The 1275 bp gene was overexpressed in two different vectors viz., pET28a and pCOLD TF and investigated for variable soluble expression, purification and activity of the recombinant enzyme with optimum pH and temperature of enzyme as 6 and 55 degrees C, respectively. The sequence was characterized in silico by subjecting it to homology search, multiple sequence alignment and phylogenetic tree construction revealing its identity to other trehalases which belong to glycoside hydrolase family 37. The deduced amino acid sequence and modeled 3D structure of DmTre possessed all features of trehalase superfamily, including signature motifs and catalytic domain. The active site pocket of recombinant DmTre was compared with the crystal structure of E. coli trehalase identifying Glu424 and Asp226 as the putative catalytic residues. Additionally, enzyme-substrate docking suggests possible involvement of other residues in the catalysis along with Asp226. The present study holds significance in understanding the structural aspects of Drosophila trehalase in spite of unavailabilty of eukaryotic trehalase crystal structure. (C) 2016 Elsevier B.V. All rights reserved.